2020
DOI: 10.1007/s10877-020-00595-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact thermography-based respiratory rate monitoring in a post-anesthetic care unit

Abstract: In patients at high risk of respiratory complications, pulse oximetry may not adequately detect hypoventilation events. Previous studies have proposed using thermography, which relies on infrared imaging, to measure respiratory rate (RR). These systems lack support from real-world feasibility testing for widespread acceptance. This study enrolled 101 spontaneously ventilating patients in a post-anesthesia recovery unit. Patients were placed in a 45° reclined position while undergoing pulse oximetry and bioimpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Twelve studies of contactless devices provided respiratory rate range. Of these, seven studies of contactless devices contained respiratory rates <8 breaths.min ‐1 [13, 43, 46, 60, 62–64] and five recorded rates >30 breaths.min ‐1 [13, 43, 46, 60, 63]. Plots demonstrating the range of vital signs in wearable heart rate devices are in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies of contactless devices provided respiratory rate range. Of these, seven studies of contactless devices contained respiratory rates <8 breaths.min ‐1 [13, 43, 46, 60, 62–64] and five recorded rates >30 breaths.min ‐1 [13, 43, 46, 60, 63]. Plots demonstrating the range of vital signs in wearable heart rate devices are in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight wearable devices across 23 studies [13, 17–19, 21, 23, 25, 26, 28, 29, 31, 33, 36–38, 40–42, 48–50, 68, 69] and 10 contactless devices across nine studies [13, 42, 46, 51–53, 67, 70, 71] had enough data to assess the accuracy of heart rate compared with the reference standard with a Bland–Altman plot. There were 31 respiratory rate devices over 28 studies of wearable devices [13, 17, 18, 21–29, 31, 33, 35, 41, 54–60, 65, 66, 72, 73] and 13 devices over 13 studies of contactless devices [13, 43, 46, 53, 60, 62–64, 70, 71, 74–76] that utilised Bland–Altman plots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 27 extubated intensive care patients, Chan et al[ 49 ] demonstrated that respiration rate monitoring based on infrared thermography agreed with gold standard chest movement counting by two observers (best R = 0.96) and outperformed respiration rate monitoring based on the often-used method of ECG-derived bioimpedance. Similarly, in a post-anesthesia recovery unit, Kwon et al[ 50 ] reported that respiration rate monitoring based on infrared thermography in 101 spontaneously breathing patients yielded an R 2 = 0.9 between infrared thermography and manual counting based on the clinical monitor. This extends earlier work by Hochhausen et al[ 51 ] who reported an accuracy (r = 0.607) of infrared thermography respiration rate monitoring compared to respiration rate derived from ECG-based bioimpedance in 28 postoperative patients.…”
Section: Unobtrusive Respiratory Rate Monitoring At the Edge Of Trans...mentioning
confidence: 99%